Prospects for the Development of Investment Activities of Insurance Organizations - Qumri Isoyevna, Namozova (Research Parks Publishers, 2023)
The relevance of the research topic lies in the need to improve the efficiency of the investment activities of national insurance organizations, since, taking into account world experience, investment activities should provide the main income of insurance companies, which will allow, in a significant way, to regularly increase equity capital and improve financial condition, and in general, provide the possibility of developing the national insurance market and having a positive impact on the development of the national economy.